Characterization of Cu3SnS4 nanoparticles and nanostructured flowers synthesized by a microwave-refluxing method - Narongrit Tipcompor (2018)
Cu 3 SnS 4 nanoparticles and nanostructured flowers were synthesized by 100, 300, 600, and 800 W microwave refluxing of the mixture containing 3 mmol CuCl 2 ·2H 2 O, 1 mmol SnCl 2 ·2H 2 O, and 4 mmol thiosemicarbazide (NH 2 NHCSNH 2 ) in 50ml ethylene glycol (HOCH 2 CH 2 OH). X-ray diffraction (XRD), selected area electron diffraction (SAED), X-ray photoelectron spectroscopy (XPS), scanning and transmission electron microscopy (SEM and TEM), Raman analysis, and photoluminescence (PL) spectrophotometry revealed the morphology transformation of pure tetragonal Cu 3 SnS 4 with nanoparticles at 100W into three-dimensional (3D) hierarchical flower-like structure at 800 W, including the presence of 2Cu + , Cu 2+ , Sn 4+ , and 4S 2- containing in the sulfide, the PL emission of the 3D hierarchical flower-like Cu 3 SnS 4 at 366 nm, and the prominent Raman peak of Cu-Sn vibration at 319 cm -1 . In this research, a formation mechanism was also proposed according to the experimental results. © 2013 The Japan Society of Applied Physics.